Experimental and numerical investigation of footing behaviour on multi-layered rubber-reinforced soil - Moghaddas Tafreshi, Seyed Naser; Joz Darabi, Naser; Tavakoli Mehrjardi, Gholamhosein; Dawson, Andrew (Taylor & Francis, 2016)
This paper describes the beneficial effects of multiple layers of rubber–sand mixture (RSM). The plate load tests, using circular plate of 300 mm diameter, were performed at an outdoor test pit, dug in natural ground with dimensions of 2000 × 2000 mm in plan and 720 mm in depth to facilitate realistic test conditions. The rubber used in the RSM layers was granulated rubber, produced from waste tires. The optimum thickness of the RSM layer was determined to be approximately 0.4 times the footing diameter. By increasing the number of RSM layers, the bearing capacity of the foundation can be increased and the footing settlement reduced. The influence of the number of RSM layers on bearing capacity and settlement become almost insignificant beyond three layers of RSM, particularly at low settlement ratios. At a ratio of settlement to plate diameter of 4%, the values of bearing pressure for the installation with one, two, three and four layers of RSM were about 1.26, 1.47, 1.52 and 1.54 times greater, respectively, than that for the unreinforced installation. Layers of the RSM reduced the vertical stress transferred through the foundation depth by distributing the load over a wider area. For example, at an applied footing pressure of 560 kPa, the transferred pressure at a depth of 570 mm was about 58, 45 and 35% for one, two and three layers of RSM, respectively, compared to the transferred stress in the unreinforced bed. By numerical analysis, it was found that the presence of soil-rubber layers resulted in expansion of passive zones in the foundation due to the effectiveness of the confinement provided by the rubber inclusions, and this tends to make the bed deflect less. On the basis of this study, the concept of using multiple RSM layers has not only been shown to improve the performance of foundations under heavy loading, but also, the environmental impacts of waste tires are attenuated by re-using their rubber as part of a composite soil material in civil engineering works.